Santa Rosa festejada: la exaltación del criollismo en Festiva Pompa de Juan Meléndez (1671) - Valero Juan, Eva (2019)
The analysis of the relationship of Juan Meléndez Festiva pompa, culto religioso, veneración reverente, fiesta, aclamación, y aplauso: a la feliz beatificación de la bienaventurada virgen Rosa de S. María (Lima, 1671) sheds light on the function of relationships of parties as speeches that throughout the seventeenth century contributed to the conformation of identity in the viceregal context. The use of Santa Rosa for the realization of an Americanist claim against Spain makes this relationship a fundamental text of the criollismo at the end of the seventeenth century. To the study of the text in this sense, and in connection with another work by the same author, Tesoros verdaderos de las Indias (1681), this article is dedicated.